2021
DOI: 10.33448/rsd-v10i14.20690
|View full text |Cite
|
Sign up to set email alerts
|

Primary metabolism and initial development of grafted black pepper seedlings

Abstract: The production of black pepper seedlings through grafting is a promising strategy to mitigate the effect of environmental stresses, such as drought, that limit its cultivation. However, studies on compatibility between grafts and rootstocks are still scarce, especially considering the wild species of the genus Piper and the cultivated genotypes of black pepper. The objective of this work was to evaluate the relationship between primary metabolism and the development of black pepper seedlings obtained through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
(34 reference statements)
1
9
0
2
Order By: Relevance
“…Hand.-Mazz., however, was considered incompatible, as it did not show a good establishment between graft and rootstock (John et al 2020). Initial compatibility has also been reported for P. tuberculatum (Crasque et al 2021). Initial compatibility is very important for the successful production of grafted seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hand.-Mazz., however, was considered incompatible, as it did not show a good establishment between graft and rootstock (John et al 2020). Initial compatibility has also been reported for P. tuberculatum (Crasque et al 2021). Initial compatibility is very important for the successful production of grafted seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al (2020) observed 82.0% of P. nigrum graft survival on P. colubrinum. Crasque et al (2021) considered P. aduncum grafted on cv. Bragantina compatible, as in the present study, due to the lower impediment of carbohydrate flow, aerial part formation, and survival.…”
Section: Rootstocksmentioning
confidence: 99%
See 1 more Smart Citation
“…A avaliação das cultivares nos tutores ocorreu conforme as variáveis de crescimento, altura das plantas, diâmetro do caule, e número de ramos ortotrópicos de quatro plantas escolhidas ao acaso para cada cultivar por tutor, assim como o comprimento do pecíolo, e a largura, o comprimento e a espessura de 40 folhas adultas, enquanto que para avariáveis de produção, o tamanho da espiga sem pedúnculo, o peso e o número de frutos por espiga foram tomados de 20 espigas. Os dados obtidos foram submetidos à análise de variância, para experimento em blocos ao acaso, utilizando o software SISVAR (Ferreira et al, 2021). As médias foram comparadas aplicando-se o teste Tukey ao nível de 0,05 de probabilidade para verificação de efeito significativo.…”
Section: Metodologiaunclassified
“…A espécie é autógama e nas condições amazônicas a floração ocorre entre os meses de dezembro a abril, durante a época de chuva na região, a polinização ocorre por geitonogamina, em que a água auxilia na dispersão do pólen e a colheita ocorre seis meses após a fecundação (Poltronieri et al, 2020). A multiplicação para o cultivo comercial ocorre por meio de estacas de um a três nós, retiradas do terço médio da planta, permitindo a obtenção de pimentais homogêneos e produtivos no primeiro ano de cultivo (Albuquerque & Duarte, 1979;Crasque et al, 2021).…”
Section: Introductionunclassified